Type 2 Diabetes Mobile Application for Supporting for Clinical Treatment: Case Development Report - Thinnukool, Orawit; Khuwuthyakorn, Pattaraporn; Wientong, Purida; Suksati, Benjamas; Waisayanand, Nipawan (International Journal of Online and Biomedical Engineering (iJOE), 2019)
As clinical treatments for type-2 diabetes patients using mobile application on smartphones have become more widely practiced, the technology has enabled patients to easily control and monitor their blood sugar levels themselves. Although, the technology development provides more options to improve type-2 diabetes treatment, not all applications developed are suitable for the real treatment as there might be different situations and treatments for different cases. Research questions occurred while attempting to develop a diabetes mobile application as a supportive learning and self-monitoring tool. These research questions are the followings: How are patients enabled to use the diabetes mobile application effectively? And what are necessary functions of the mobile application for diabetes? The objective of this research are (1) to analysis, design, and development of a type-2 diabetes mobile application (T2DM) (2) to test the application. The method starts with collecting users’ requirements from diabetes experts, type-2 diabetes patients and their relatives for using the type-2 diabetes literacy-learning tool. Five qualified diabetes experts and five pairs of diabetes patients with their relatives were investigated for gathering users’ requirements that lead to necessary functions for the development. After the T2DM is completely developed, 18 medical staffs and 20 diabetes patients and patient relatives tested the T2DM by using the application. Conclusion: When designing the more effective T2DM, developing of necessary functions by users’ involvement ensures that requirements were analyzed and tested. It has been found that the nutrition function is the most significant piece of information for the T2DM, and also the key point of the development. At the same time, the functions for blood sugar recording and information sending are the most supportive and helpful functions for users.